Reforming the Nigerian National Assembly for Legislative Effectiveness: Issues, Constraints and Way-Forward: Array - Bakare, Adebola Rafiu; Bello, Muhammed Lawan (Acta Universitatis Danubius. Administratio, 2020)
The persistent refusal of the Nigerian legislators to make public their actual earnings had continue to generate comments which among other issues have led to agitations for the reform of the National Assembly to reduce the cost of governance in Nigeria, especially in the wake of the scrapping of the Senegalese Senate in 2012 and the recent ‘yes’ vote to scrap the upper chamber in Mauritania in 2017. In addition, the intensity of the recent claims by a federal lawmaker, Honourable Abdulmumin Jibrin on the pattern of running the National Assembly in terms of scandalous extra-budgetary allowances of lawmakers and secrecy of legislative activities among others have become too weighty to be ignored which make a research into these issues inevitable. It is against this backdrop that this paper examines the issues and arguments surrounding the calls for reforming the National Assembly. The paper adopted mixed-method research design and found that the official salaries and allowances of Nigerian legislators are relatively low in comparison with what obtains in other climes. It also found some elements of lopsidedness in the House’s seats distribution as some states with lower population are given more seats than some with higher population.